Building Knowledge in the Oil Market. (January 2022) - Martín-Bujack, Karin; Figuerola-Ferretti, Isabel; Corzo, Teresa; Paraskevopoulos, Ioannis
In this paper, we establish the process of building up knowledge in oil markets using market observables from oil derivatives trading activity and a measure of academic publication volume. We establish the way in which knowledge feeds back into market activity via the channels of different regulation policies. Employing a textual analysis based on information from Web of Science and Scopus databases, we build our knowledge proxy using the total number of publications, and run a cointegration test for the 2000 to 2020 period against two measures of trading activity. We find leadership of the market activity variable when considering the whole sample. The influence of knowledge on market activity is captured in the aftermath of the Global Financial Crisis. Furthermore, the interaction of both variables is reinforced in 2014 after the final implementation of the Volcker rule and during the onset of the crude oil price collapse. Our results shed light to the need of monitoring the joint dynamics of publishing and trading activity to improve the resource allocation and financial product innovation process.